Le sens des rites scolaires - Denis Jeffrey (Recherches en Éducation, 2015)
We are interested in the rituals dedicated to teachers and students in a school setting. An impressive number of rituals, which are more or less developed, coded, and mastered, maintain rhythm and organize the students’ and teachers’ school life. From it’s inception, has pedagogy’s aim not been maintaining and sustaining school order by identifying specific teacher and student behaviours? In fact, a child becomes a student by adopting highly ritualized behaviours that make him a student. Teacher’s also have specific behaviours that make hime a teacher. In this way, we are saying that their are gestures, a way of being, a way of doing, a language, a dress code, that is a general self-composition, that identifies an individual as a teacher or a student. In this article, the focus is on the rituals that create these school identities.